SURVEY PAPER: SOFTWARE AUTOMATED TESTING TOOL USING SYSTEMATIC LITERATURE REVIEW METHOD - Absharina, Dheanda; Fahirah, Fahirah; Agustina, Fenni (LPPM Universitas Nusa Mandiri, 2020)
Software testing is one of the most important roles in successful software development. The increasing complexity of software development requires the development team to use automated testing tools to test the quality and functionality of the application. In software testing, choosing a testing tool must be appropriate and in accordance with the software to be tested. Using the Systematic Literature Review method, this research collects and analyzes previous survey papers from 2 keywords,